Investigating the experiences of deaf or hard of hearing children participating in sport - Somerset, Sarah (2020)
This thesis investigates sports participation in deaf or hard of hearing children. Participation in sport is evidenced to have a positive effect on mental and physical health. In children, it can help to facilitate socialisation. For deaf or hard of hearing children the sports environment exposes them to challenges and opportunities they may not otherwise gain in life.